Phytochemical composition, antimicrobial activities, and cholinesterase inhibitory properties of the lichen Usnea diffracta Vain - Hao, Yi-Meng; Yan, Yuan-Cong; Zhang, Qing; Liu, Bing-Qian; Wu, Chang-Sheng; Wang, Li-Ning (Frontiers in Chemistry, 2023)
Lichens are important sources of versatile bioactive compounds. Two new dibenzofurans (1-2), a multi-substituted single benzene ring (3), and two organic acid compounds (4-5) along with 25 known compounds (6-30) were isolated from the lichen Usnea diffracta Vain.. Their structures were identified by physicochemical properties and spectral analyses. Compounds 1-30 were tested for inhibitory activities against Staphylococcus aureus, Escherichia coli and Candida albicans by disk diffusion method and microdilution assay respectively. Compound 3 showed moderate inhibitory activities against S.aureus and E.coli with IZ of 6.2 mm and 6.3 mm. Depside 10 exhibited good activity against S.aureus and C. albicans with 6.6 mm and 32 μg/ml, respectively. Acetylcholinesterase inhibitory activities of Compounds 1, 2, 6-8 with the characteristic dibenzofuran scaffold were evaluated var Anti-AChE assay and Molecular docking study. Compound 2 could better inhibit AChE at the concentration of 0.3 μmol/ml with value of 61.07±0.85 %. Molecular docking study also demonstrated that 2 had the strongest binding affinity among five dibenzofurans and the ‘-CDOCKER Energy’ value was 14.4513 kcal/mol.